Analisis Penyelesaian Konflik Etnis Pandit Berdasarkan Prinsip Mengelola Konflik Etnis Menurut Barbara Harff dan Ted Robert Gurr - Zahra, Nazhifah; Rifai, Maulana; Marsingga, Prilla (Peneliti.net, 2025)
Violent anti-Hindu riots in 1984 and 1986 were followed by concerted efforts to ethnically cleanse Kashmiri Hindu Pandits. As many as 350,000 Kashmiri Hindu Pandits became refugees in their homeland. Barbara Harff and Ted Robert Gurr's principles promote ways to manage ethnic and religious conflict, pressure to respect minority rights, democratic institutions, self-determination, international intervention, and coercion to end violence. This research examines Pandit-ethnic conflict resolution using a qualitative approach and literature review methodology based on the principles put forward by Barbara Harff and Ted Robert Gurr. The data collected came from primary sources such as books and academic articles by Harff and Gurr and secondary sources such as journals, books, research reports and documents related to the Pandit ethnic conflict. This theoretical framework emphasizes the importance of respecting the civil and political rights of ethnic and religious minority groups to ensure justice, equality, and long-term peace and stability.